Sex logics: Negotiating the prison rape elimination act (PREA) against its’ administrative, safety, and cultural burdens - Rudes, Danielle S. (Punishment & society, 2021)
The Prison Rape Elimination Act (PREA) reforms correctional institutions via administrative mechanisms and represents a major shift in both correctional policy and workplace practice. Using qualitative data within six prisons in one U.S. state, finding suggest that staff view PREA as an administrative, safety, and cultural burden, which creates a misalignment of institutional logics. Rather than seeing themselves as central to eliminating prison sexual misconduct/violence, staff see PREA as interfering with their “real” custody/control work. This misalignment has major implications for the productive implementation and use of PREA and the broader shift to administrative rather than legal processes for institutional reform.